2012
DOI: 10.1002/cam4.5
|View full text |Cite
|
Sign up to set email alerts
|

Emphasizing the role of Wnt5a protein expression to predict favorable outcome after radical prostatectomy in patients with low‐grade prostate cancer

Abstract: Wnt5a, a member of non-canonical wingless-related MMTV integration site family is a secreted glycoprotein that plays important roles in development and disease. Recent studies have shown that Wnt5a protein levels are up-regulated in prostate cancer, but contrasting reports exist on the role of Wnt5a to predict outcome after radical prostatectomy in patients with localized prostate cancer. Our group has recently shown that preserved high protein expression of Wnt5a in prostate cancer is associated with longer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…Using two well‐defined cohorts of patients with prostate cancer, we showed that the expression of WNT5A is increased in prostate cancer tissue compared with nonmalignant prostate tissue. This finding is in line with several other studies, confirming high levels of WNT5A in prostate cancer tissue . Additionally, WNT5A expression was highly correlated with the expression of its cognate receptor FZD5, suggesting that FZD5 could mediate, or even amplify, WNT5A‐induced effects in prostate cancer.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Using two well‐defined cohorts of patients with prostate cancer, we showed that the expression of WNT5A is increased in prostate cancer tissue compared with nonmalignant prostate tissue. This finding is in line with several other studies, confirming high levels of WNT5A in prostate cancer tissue . Additionally, WNT5A expression was highly correlated with the expression of its cognate receptor FZD5, suggesting that FZD5 could mediate, or even amplify, WNT5A‐induced effects in prostate cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Our study further indicates that patients with high tumor expression of WNT5A have a longer overall survival and suggests a tumor‐suppressive function of WNT5A in prostate cancer. This result is supported by the work of a Swedish group performed in two different cohorts ( n = 263 and n = 503), which showed that patients with high WNT5A expression in the tumor have a longer biochemical relapse‐free survival after radical prostatectomy . Even though our TMA has an overrepresentation of high‐grade tumors (>60% with Gleason score >7) compared with the Swedish studies, which have included more patients with low‐grade tumors (>75% with Gleason score 3 + 4 in both studies), our study has reached a similar conclusion.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It has previously been shown that preserved expression of WNT5A in the primary tumor is associated with increased time to biochemical recurrence in patients with low-grade prostate cancer [ 26 ]. Moreover, patients with high endogenous WNT5A levels show a longer survival time and an overall better outcome compared to patients with low WNT5A levels [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some reports contradict the protumorigenic effect of WNT-5A, correlating high WNT-5A expression with improved outcomes in localized, lowgrade prostate cancer [94][95][96] . In other cancers such as liver, breast and lung, the WNT-5A-FZD2 complex has been reported to associate with the protein tyrosine kinase FYN and signal transducer and activator of transcription 3 (STAT3) to promote the epithelial-mesenchymal transition (EMT) and cell migration 97 .…”
Section: [H1] Wnt Ligands and Their Receptorsmentioning
confidence: 99%